2008
DOI: 10.1159/000152038
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Ovarian Differentiation: <i>Rspo1</i>, a Major Player

Abstract: In mammals, the sex of the embryo is determined during development by its commitment either to the male or female genetic program regulating testicular or ovarian organogenesis. Major steps towards unraveling sex determination in mammals are achieved by the identification of key genes involved in human pathologies and the application of mouse genetics to analyze their function. While the expression of Sry and Sox9 is sufficient to induce the male devel- opmental program, the molecular pathways that specify ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 103 publications
3
61
1
1
Order By: Relevance
“…The ovarian part contained corpora albicans, indicating the presence of a former follicle. Consistent with this finding, adult XX Rspo1 K/K mice display sex reversal and are characterized by ovotestes in which the testicular part, evidenced by the presence of male-like seminiferous tubules with Sertoli cells and interstitial tissue, can form the main part of the mutant gonad, giving it the appearance of a hypoplastic testis (Chassot et al 2008b). Within the ovarian part, the presence of large abnormal cysts was noticed in 11-week-old mice (Chassot et al 2008a).…”
Section: R99supporting
confidence: 71%
“…The ovarian part contained corpora albicans, indicating the presence of a former follicle. Consistent with this finding, adult XX Rspo1 K/K mice display sex reversal and are characterized by ovotestes in which the testicular part, evidenced by the presence of male-like seminiferous tubules with Sertoli cells and interstitial tissue, can form the main part of the mutant gonad, giving it the appearance of a hypoplastic testis (Chassot et al 2008b). Within the ovarian part, the presence of large abnormal cysts was noticed in 11-week-old mice (Chassot et al 2008a).…”
Section: R99supporting
confidence: 71%
“…Indeed, it has been proposed that Wnt4 can act on luminal cells (Hiremath et al 2007;Joshi et al 2010). Recent studies have demonstrated that Rspo1 and Wnt4 cooperate during early gonad proliferation in ovary differentiation (Chassot et al 2008(Chassot et al , 2012Tomizuka et al 2008). It will be interesting to understand whether such cooperation mediates the influence of hormones in these processes.…”
Section: Rspo1 As a Novel Hormone Mediatormentioning
confidence: 99%
“…-/-males are normally fertile and do not exhibit gross gonadal abnormalities (Chassot et al, 2008a).…”
Section: Rspo1mentioning
confidence: 99%